Recent Trends in Income, Racial, and Ethnic School Readiness Gaps at Kindergarten Entry - Sean F. Reardon; Ximena A. Portilla (SAGE Publishing, 2016)
Academic achievement gaps between high- and low-income students born in the 1990s were much larger than between cohorts born two decades earlier. Racial/ethnic achievement gaps declined during the same period. To determine whether these two trends have continued in more recent cohorts, we examine trends in several dimensions of school readiness, including academic achievement, self-control, externalizing behavior, and a measure of students' approaches to learning, for cohorts born from the early 1990s to the 2000-2010 midperiod. We use data from nationally representative samples of kindergarteners (ages 5-6) in 1998 (  n = 20,220), 2006 (  n = 6,600), and 2010 (  n = 16,980) to estimate trends in racial/ethnic and income school readiness gaps. We find that readiness gaps narrowed modestly from 1998 to 2010, particularly between high- and low-income students and between White and Hispanic students.